Perspectives Review of Management in Renal Injury: A Single Centre Experience - P, Kavin Raj; Kumar, Kaillash; Cheong, YT (IIUM Medical Journal Malaysia, 2019)
Introduction: Renal injury occurs in 1%–5% of all trauma cases. The objective of this retrospective study is to register a clinical audit on renal injury management of a single center. Materials and Methods: All renal–related trauma cases presented to Penang Hospital between August 2015 and July 2017 were included in this audit. These injuries were classified using American Association for the Surgery of Trauma (AAST) renal injury scale. Results: A total of 145 cases of renal trauma were audited; of which 40 cases of Grade I injury, 30 cases of Grade II, 45 cases of Grade III and 30 cases constituting Grade IV and V injury. Broadly, these patients were managed via two main approaches; 138 (95.27%) via conservative approach and 7 (4.83%) via surgical intervention. Among those who underwent surgical intervention, 3 had emergency nephrectomy performed while the other 4 had ureteric stenting. Conclusion: Literature review had shown up to 95% of renal injuries can be successfully managed conservatively, especially in cases of blunt trauma. The clinical audit of our center demonstrates that the perspective of renal injury management is in par with internationally acclaimed general consensus; hence affirms the feasibility of conservative management in a vast number of cases, with a prudential role for surgical intervention in severe injuries.